PERANCANGAN APLIKASI MONITORING KUALITAS AIR BERBASIS ANDROID - Armita, Angella; Hoendarto, Genrawan; Kartono, Kartono (INTEKSIS, 2024)
The importance of water for human survival has become crucial to ensuring its viability before being used and consumed, especially water for hygiene and sanitation purposes. To measure water quality, it is necessary to test the parameters that have been standardized by the government. So from that, it takes a device to measure the water quality adequately to know the water condition. In the design of the system, the prototype consists of a temperature sensor to detect temperature, a Total Dissolved Solid (TDS) sensor to measure the amount of solute solids, and a pH sensor for measuring the acidity or alkalinity of water, all controlled by NodeMCU ESP32. To facilitate monitoring of water quality, the measurements performed by the sensor will be displayed in an Android application. During the test, the temperature sensor obtained an accuracy of 98.15%, the TDS sensor received an accurate value of 98,82%, and the pH sensor achieved a precision of 97.52%. The readings from the data obtained from the prototype monitoring of water quality are close to the readings of the comparison. From the test results, it can be stated that the water quality monitoring prototype works well. Keywords— Android, Water Quality, Prototype, NodeMCU ESP32.